VACCINE FOR NEUROCYSTICERCOSIS: A PRESENT UPDATE - Wiwanitkit, Viroj (Malang Neurology Journal, 2018)
Cysticercosis is an important tropical parasitic worm infestation. This infection can result in cyst in any organs of human beings including to brain. The brain involvement of cysticercosis or neurocyticercosis is an important neurological infection that can cause serious neuruological problem. A good sanitation is the basic prevention for cysticercosis. Nevertheless, the hope is the use of vaccination. Here, the author briefly reviews and discusses on the present situation of neurocysticercosis vaccine.